Urban sprawl in a megaregion: A multiple spatial and temporal perspective. (January 2019) - Zhou, Weiqi; Jiao, Min; Yu, Wenjuan; Wang, Jia
Highlights: Urban sprawl was quantified at multiple spatial and temporal scales. Large variations in annual growth rates, and degrees of sprawl among cities and counties. We found increasing urban sprawl in density, but less sprawl in centrality. We found nonlinear relationships between measures of sprawl and total area and proportional cover of developed lands. Abstract: Numerous studies have been conducted to examine the characteristics of urban sprawl at multiple scales, ranging from neighborhood, to city, and metropolitan statistical area. However, few studies have investigated urban sprawl in a megaregion, particularly from a multiple spatial and temporal scale perspective. Focusing on the Beijing-Tianjin-Hebei (BTH) megaregion, one of the largest urban megaregion in China, we quantified the multiscale characteristics of urban sprawl, and how they changed by time, using a combination of density (land consumption per capita) and centrality (Moran's I coefficient of developed land) indicators. We found: (1) The BTH urban megaregion experienced rapid urban expansion during 1984–2015, with large variations in annual growth rates, and the two measures of sprawl among cities and counties. (2) Land consumption per capita in the megaregion had a clear increasing trend at all three levels, suggesting decreased density and land use efficiency, and thus increased urban sprawl. (3) In contrast, Moran's I coefficient had trends of increase at multiple scales, suggesting urban developed lands tended to become more clustered spatially. (4) Nonlinear relationships between the two measures of sprawl and the total area and proportional cover of developed lands at county level. Land consumption per capita first increased, and then decreased with the increase of the total area and proportional cover of developed lands, following the pattern of the reversed U shape curve. Similar patterns were found for Moran's I coefficient. Our results highlight the importance of quantifying urban sprawl at multiple temporal and spatial scales, using multi-dimensional indicators. Results from this study can enhance our understanding on the spatiotemporal characteristics of urban sprawl, and can provide important insights to inform public policy for urban growth management and planning.